Difficulties encountered by Francophone Teachers in the teaching of English Language in Cameroon Primary Schools - Atabong Nee Alemanjoh Maria Nkea; Edi Suprayetno; Missi Tri Astuti (English Lecturers and Teachers Association (ELTA), 2022)
Abstract This study aims at earmarking some related issues regarding the teaching of English language to francophone pupils by francophone teachers. As regard the theoretical framework, the connectionism, acculturation and teaching-learning theories was used. The methodology in this study is the quantitative and qualitative approach and the random sampling technique is used in the selection of the population under study. The research instruments that are used are the interview and observation. The instruments were administered taking into consideration the pronunciation of sounds (phonology) pluralisation of nouns, sentence construction, the use of articles and tenses (morpho-syntax). A total of 73 teachers from six primary schools were interviewed and observed. The frequency distribution technique is used for analyzing data. Analyzing the data collected proves that the francophone teachers have difficulties in pronouncing some sounds in the English language. The teachers equally have difficulties in putting some nouns in their plural forms, constructing of sentences and correct use of articles and tenses. From the findings, the researcher made some recommendations. That a solid foundation should be laid during the initial training on the teaching of the English language. Secondly, in-service training should be encouraged for teachers already in the field. The researcher also suggested that Pedagogic Inspectors in charge of bilingualism should organize regular pedagogic seminar on English language for the francophone teachers. Keywords: Difficulties, ELT, Francophone Teachers